Thrust Measurement of an Integrated Multi-Sensor Micro-Newton Cold Gas Thruster - Songcai Lu; Yong Gao; Haibo Tu; Xudong Wang; Xinju Fu; Gang Meng; Jun Long; Xuhui Liu; Yong Li (Aerospace)
In recent years, cold gas thrusters have been successfully deployed in numerous missions, showcasing their exceptional reliability and enabling ultra-precise space operations across a broad thrust range. This article introduces an integrated cold gas thruster that integrates flow, pressure, and displacement sensors. The thrust range of this thruster can exceed 1000 μN at most, and the resolution can reach up to 0.1 μN at low thrust. The results of the high-precision displacement sensor are good, showing that the thruster performs well in terms of flow control accuracy and thrust output sensitivity. The measurement accuracy of the force frame itself is also excellent, and it can detect small thrust changes of 0.1 μN. The thrust noise level of the thruster is good, comparable to the standard noise levels of the experimental environment.